DEVELOPMENT OF THE KEMENI MEDIAN AS FINAL GROUP OF BENEFITS - Камишин, В. В. (Science-based technologies, 2013)
In despite of emergence possibility of so-called group deformations during the collective choice realization process, the group decision is still more acceptable than the individual one, because it is characterized by a number of positives. One of the strategies of collective decisions is to determine the group benefits system under which an ordering of the set of studied alternatives, by the most acceptable to least acceptable, is meant. Typically, this applies summing and averaging the ranks of alternatives in the individual benefits systems, which can lead to the synthesis of contradictory (marginal) views. Even implementing a multi-step iterative procedure for application of pattern recognition theory for detecting and getting rid of these marginal thoughts, and proving a significance for Kendall’s coefficient of concordance, which characterizes the degree of consistency of students- experts’ opinions on a set of typical indiscipline features, to a high statistical veritable at the significance level a = 0, 2% of the value of W = 0,7988, will still remain a question of the final "genuine" group system of benefits determination.Taking into account that ranks of alternatives are qualitative linguistic estimations, which does not apply the usual methods of mathematics, the question of nonparametric definition of group benefits is raised. The received empirical median value has an extremely high degree of convergence (Spearman's rank correlation coefficient is almost perfect - RS = 0,9984) with consensual group system of preferences, built by the strategy of summing and averaging of ranks.